2018
DOI: 10.3390/v10030117
|View full text |Cite
|
Sign up to set email alerts
|

San Wu Huangqin Decoction, a Chinese Herbal Formula, Inhibits Influenza a/PR/8/34 (H1N1) Virus Infection In Vitro and In Vivo

Abstract: The San Wu Huangqin Decoction (SWHD), a traditional Chinese medicine formula, is used to treat colds caused by exposure to wind-pathogen, hyperpyrexia, infectious diseases and cancer; moreover, it is used for detoxification. The individual herbs of SWHD, such as Sophora flavescens and Scutellaria baicalensis, exhibit a wide spectrum of antiviral, anti-inflammatory, antibacterial, anticancer and other properties. The Chinese compound formula of SWHD is composed of S. flavescens, S. baicalensis and Rehmannia glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…Traditional Chinese herbal medicine therapy is a mixture of Chinese herbs prescribed by Chinese herbalists depending on the differentiation of the patient's syndrome according to Chinese diagnostic patterns (inspection, listening, smelling, inquiry, and palpation). Studies have reported that Chinese herbal formula, such as San Wu Huangqin Decoction, Lianhuaqingwen Capsule, and Yinhuapinggan granule, possesses antiviral effects, which might be associated with blocking of the proliferation and replication of the viral particles, and that they might be able to improve lung damage by influenza viruses [14][15][16]. During the SARS epidemics, traditional Chinese herbal medicine treatments were reported to have successfully prevented and treated SARS [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese herbal medicine therapy is a mixture of Chinese herbs prescribed by Chinese herbalists depending on the differentiation of the patient's syndrome according to Chinese diagnostic patterns (inspection, listening, smelling, inquiry, and palpation). Studies have reported that Chinese herbal formula, such as San Wu Huangqin Decoction, Lianhuaqingwen Capsule, and Yinhuapinggan granule, possesses antiviral effects, which might be associated with blocking of the proliferation and replication of the viral particles, and that they might be able to improve lung damage by influenza viruses [14][15][16]. During the SARS epidemics, traditional Chinese herbal medicine treatments were reported to have successfully prevented and treated SARS [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This is the third reported case worldwide of contact dermatitis from S. baicalensis . S. baicalensis is a plant found in Russia, China, Japan, Korea, and Mongolia, having antioxidant, antitumoral, and antiviral properties. As it is being used increasingly, we may witness more cases of contact allergy to it.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that Chinese herbal formula, such as San Wu Huangqin Decoction, Lianhuaqingwen Capsule and Yinhuapinggan granule, possess antiviral effects, which might be associated with blocking of the proliferation and replication of the viral particles, and that they might be able to improve lung damage by influenza viruses. [14][15][16] During the SARS epidemics, TCM treatments were reported to have successfully prevented and treated SARS. [17][18][19] Furthermore, TCM combined with western medicine treatment regimen reduced adverse events and other complications induced by glucocorticoid, antibiotic and antiviral treatments.…”
Section: Traditional Chinese Medicine (Tcm) Therapy Is a Mixture Of Cmentioning
confidence: 99%